Idiopathic epilepsy in dogs is associated with dysbiotic faecal microbiota - Marco Silvestrino; Mattia Pirolo; Angelica Bianco; Stefano Castellana; Laura Del Sambro; Viviana Domenica Tarallo; Luca Guardabassi; Andrea Zatelli; Floriana Gernone (Animal Microbiome)
Abstract Background The gut microbiota plays a crucial role in modulating various physiological and pathological processes through its metabolites, including short-chain fatty acids (SCFA), which impact immune system development, gastrointestinal health, and brain functions via the gut-brain axis. Dysbiosis, an imbalance in gut microbiota composition, has been linked to neuroinflammatory and neurodegenerative conditions, including epilepsy. In dogs, idiopathic epilepsy has been hypothesized to be influenced by gut microbiota composition, although studies on this association are limited and show inconsistent results. Here, we compared the faecal microbiota of idiopathic epileptic drug-naïve dogs and healthy controls. To this aim, we recruited 19 idiopathic epileptic dogs and 17 healthy controls which met stringent inclusion criteria and characterized their faecal microbiome by 16 S rRNA sequencing. Results No significant differences were observed between the two groups regarding age, breed, body condition score, diet, or reproductive status, though males were significantly overrepresented in the idiopathic epileptic group. Epileptic dogs showed a marked reduction in bacterial richness and a trend towards lower evenness (α-diversity) compared to healthy controls, while no differences in community composition (β-diversity) were observed between the two groups. Moreover, a decrease in SCFA-producing bacteria, namely Faecalibacterium, Prevotella, and Blautia, was observed alongside an increase in Escherichia coli, Clostridium perfringens, and Bacteroides in epileptic dogs. Conclusions Idiopathic epileptic dogs exhibit dysbiosis, with reduced bacterial diversity, loss of beneficial genera, and overgrowth of opportunistic pathogens. These alterations in microbiota diversity and composition may contribute to epilepsy via the gut-brain axis, highlighting the need for further research to explore dietary or probiotic interventions targeting gut microbiota modulation as adjunctive therapies for managing epilepsy in dogs.